The Little Data Book on Information and Communication Technology 2012 - World Bank (Washington, DC, 2013)
Since the late 1990s access to information and communication technologies (ICTs) has seen tremendous growth driven primarily by the wireless technologies and liberalization of telecommunications markets. Mobile communications have evolved from simple voice and text services to diversified innovative applications and mobile broadband Internet. By the end of 2011, the number of mobile-cellular subscriptions reached approximately 6 billion globally. The number of individuals using the Internet has risen constantly and reached an estimated 2.4 billion while the number of fixed (wired)-broadband subscriptions reached almost 600 million at the end of 2011. The impacts of ICTs cross all sectors. Research has shown that investment in information and communication technologies is associated with such economic benefits as higher productivity, lower costs, new economic opportunities, job creation, innovation, and increased trade. ICTs also help provide better services in health and education, and strengthen social cohesion. The little data book on information and communication technology 2012 illustrates the progress of this revolution for 216 economies around the world. It provides comparable statistics on the sector for 2005 and 2010 across a range of indicators, enabling readers to readily compare economies. This book includes indicators covering the economic and social context, the structure of the information and communication technology sector, sector efficiency and capacity, and sector performance related to access, usage, quality, affordability, trade, and applications.